THE ABILITY OF STUDENTS’ READING COMPREHENSION IN ARTICLE, NEWSPAPER, MAGAZINE AND ENSYCLOPEDIA TEXT AT SECOND SEMESTER STUDENTS - Wahyuningsih, Destri; Syafitri, Nova Runi (Ensiklopedia of Journal, 2021)
The purpose of this research is to know the ability of students and the factors that influence reading comprehension in article, newspaper and magazine texts at second semester students at STKIP Insan Madani Airmolek. The researcher used Descriptive Analysis Research. In this research, researcher wants to know the ability of students’ reading comprehension in article, newspaper, and magazine texts and to describe the factors that influence in reading comprehension: vocabulary, fluency, critical thinking and active reading. This research used the formulation total percentage of the result students ability in reading comprehension and describe the factors that influence in reading comprehension texts. By analyzing the students’ reading comprehension test, the researcher knew obtained their total scores of the result were 47,5% score.  From the test answers, the researcher describes the factors that influence in reading comprehension are vocabulary, fluency, critical thinking and active reading. That all of indicates that the students did not understand well in reading comprehension, the students still lack of vocabularies, the students were not able to get the information clearly from reading comprehension texts such as find the main ideas, factual information, details information and any else. The second semester students should more memorize the vocabulary, because vocabularies the most important factor influence reading comprehension. The students also should practice to read fast and well, it is not about fast and well, but also comprehend the contents of the text being read.